Platelet-derived microparticles and coagulation activation in breast cancer patients - Toth, Bettina; Liebhardt, Susanne; Steinig, Kerstin; Ditsch, Nina; Rank, Andreas; Bauerfeind, Ingo; Spannagl, Michael; Friese, Klaus; Reininger, Armin J. (Thrombosis and Haemostasis, 2008)
In the mid 1800s Trousseau observed cancer-associated thrombosis, of which the underlying pathogenesis still remains unknown. We performed a prospective study on platelet-derived microparticles (PMP) and their procoagulant potential in breast cancer patients. Fifty-eight breast cancer patients and 13 women with benign breast tumors were included in the study. Microparticles (MP) were examined by electron microscopy and FACS analysis using labels for annexinV (total numbers), CD61 (PMP), CD62P and CD63 (activated platelets), CD62E (endothelial cells), CD45 (leukocytes) as well as CD142 (tissue factor). Prothrombin fragment 1+2 (F1+2) and thrombin generation were measured as blood coagulation markers. Numbers of annexin V+-MP were highest in breast cancer patients with larger tumor size (T2; median = 5,637×106/l; range = 2,852–8,613) and patients with distant metastases (M1; median = 6,102×106/l; range = 3,350–7,445), and differed significantly from patients with insitu tumor (Tis; median = 3,220×106/l; range = 2,277–4,124; p = 0.019), small tumor size (T1; median = 3,281×106/l; range 2,356–4,861; p = 0.043) and women with benign breast tumor (median = 4,108×106/l; range = 2,530–4,874; p = 0.040). A total of 82.3% of MP were from platelets,14.6 % from endothelial cells and 0.3% from leukocytes. Less than 10% of PMP showed degranulation markers. Larger tumor size (T2) and metastases correlated with high counts of PMP and with highest F1+2 levels. Since prothrombin levels and thrombin generation did not parallel MP levels, we speculate that MP act in the microenvironment of tumor tissue and may thus not be an exclusive parameter reflecting in-vivo procoagulant activity.
Keywords: Platelet-derived microparticles; prothrombin fragment 1+2; thrombin generation; electron microscopy; breast cancer